Ambientes biocenóticos patagónicos y batracofauna - Cei, José Miguel Alfredo María (1969)
The existence of Telmatobiinae in Laguna Blanca (High Patagonia) suggested the carrying out of a series of investigations to esta blish the possible presence of other actual or relict forms of the same group in the extra cordilleran patagonic lakes. This was the object of the observations made in December 1965 and summarized in this paper, during which the waters of the Musters and the Colhué Huapí lakes in Chubut were explored, studying especially their biocenotic characteristics. In spite of some similarity in the ionic composition of their waters and those of Laguna Blanca, Telmatobiinae were not found; only populations of Pleurodema bufonius were seen, an especialized Amphibian predominating in the Patagonia. The author found no representatives of Amphibians in the Cardiel lake (Santa Cruz) the margins of which proved to be relatively lifeless, its waters probably presenting a too high percentage of salinity (3.020 g/l) to permit a normal development of the larval activities. Another laguna visited with the same negative results was Laguna Grande in the central plateau in Santa Cruz, together with various lakes of glacial characteristics, such as lake Viedma. Ecologic observations were made in Santa Cruz on Pleurodema bufonica where especially robust specimens were found, 6-7 cm long. Their adaptative diversification was tested repeatedly in their habitat. In Esquel (Chubut) specimens of Bufo spinulosus, probably of the form papillosus Philippi, were found, sympatric with Bufo rubropunctatus in those Antarctic woods. The sympatry of Pleurodema bufonica nad Pleurodema bibroni was registered many times in the ecotonal ambient of Chubut (Leleque). These observations reinforce the conditions of high biocenotic originality of the volcanic regions of the basaltic lagunas Northwest from Zapala (Neuquen), the typical land of Batrachophrynus patagonicus Gallardo.